Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3390/ma9030161
|View full text |Cite
|
Sign up to set email alerts
|

Compressibility of 304 Stainless Steel Powder Metallurgy Materials Reinforced with 304 Short Stainless Steel Fibers

Abstract: Powder metallurgy (P/M) technique is usually used for manufacturing porous metal materials. However, some P/M materials are limitedly used in engineering for their performance deficiency. A novel 304 stainless steel P/M material was produced by a solid-state sintering of 304 stainless steel powders and 304 short stainless steel fibers, which were alternately laid in layers according to mass ratio. In this paper, the compressive properties of the P/M materials were characterized by a series of uniaxial compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Via heat treatment; increasing of atomic vibration causes to diffusion and more atoms acts in the contact area and hence, bonding surface happens. Occurred bonding surface extends, therefore, sintering necks occurs [17,18]. this situation observed that surface of Distaloy AE alloy prepared on the 600 MPa pressure has smoother appearance than that of other alloy sample and recommended that this situation has a role on the higher heat flows of this samples according to the other samples.…”
Section: Methodsmentioning
confidence: 84%
“…Via heat treatment; increasing of atomic vibration causes to diffusion and more atoms acts in the contact area and hence, bonding surface happens. Occurred bonding surface extends, therefore, sintering necks occurs [17,18]. this situation observed that surface of Distaloy AE alloy prepared on the 600 MPa pressure has smoother appearance than that of other alloy sample and recommended that this situation has a role on the higher heat flows of this samples according to the other samples.…”
Section: Methodsmentioning
confidence: 84%
“…Dies are made of cemented carbide, pressed using hydraulic or mechanical presses. The segment delivered after compaction is called green compact [5]. The measure of a die is 50mm stature with the 10mm width.…”
Section: Ball Millingmentioning
confidence: 99%
“…In addition, the increase of sintering temperature was able to significantly enhance the tensile strength of the material. Bibo Yao et al [ 25 ] prepared a new type of 304 stainless steel powders metallurgy material with 304 stainless steel powders and 304 stainless steel short fibers as raw materials by pressing and vacuum solid-state sintering. The effects of fiber volume fraction, pressing force, and high-temperature nitriding on the compressive properties of the material were studied.…”
Section: Introductionmentioning
confidence: 99%